SOEP-IS 2014 - Individual and age differences in decisions from description and experience - Rui Mata; David Richter; Anika K. Josef; Renato Frey; Ralph Hertwig (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Empirical results suggest that individual and age-related differences in risk taking may be task dependent. Such results call into question the power of traditional measures of risk preferences, such as the choice between monetary gambles with described outcomes and probabilities, to fully and reliably capture risk behavior. The limitations of typical measures of risk taking have implications for research in different disciplines, including psychology, economics, and sociology that either aim to account for individual differences in behavior or control for such differences when trying to understand the role of tasks, groups, or institutions in producing economic and social outcomes. We propose to conduct a behavioral experiment using a within-subject design to assess the predictive power of different measures of risk taking behavior (decisions from description, decisions from experience) and to evaluate their relative power in predicting real-world outcomes. The proposed research extends the existing GSOEP database by providing behavioral assessment of individual differences that may be theoretically and practically relevant when explaining social inequalities resulting from employment, financial, and health decisions that are partly guided by individuals' risk tendencies.
Keywords: 330